ANÁ LISE OPERACIONAL, ERGONÔ MICA E DE CUSTOS DAS ATIVIDADES DE ROÇADA E PODA EM PLANTIOS FLORESTAIS - Oliveira, Felipe Martins de (2011)
The objective of this research was to conduct an operational, ergonomic and costs analysis of mowing and pruning in planted forests, carried out by manual and semi-mechanized methods, aiming to increase productivity and improve the safety and health of workers. The study was conducted in a forest services company, located in the State of Parana, Brazil. The operational analysis consisted of a time and motion study, determining the productivity and work efficiency as well an quality evaluation of the activities performed by both methods of pruning. The costs analysis was performed by the setting of production and operating costs of all studied activities. The ergonomic evaluation involved the determination of the physical workload using a heart rate monitor. In addition, there were performed a biomechanical evaluation by filming the workers in the execution of work, and the data were analyzed in the software WinOWAS (Posture Analysis) and 3DSSPP (3D Static Strength Prediction Program). The results indicated that the productivity of mowing was similar in both methods of work, while in pruning, the semi-mechanized method showed better quality and greater productivity. In both activities, production costs were higher in semi-mechanized method. The worker`s average cardiovascular load was below the recommended limit of 40% in the execution of all activities in the different methods and the work was classified as moderately heavy. The activity of manual mowing required higher physical effort of workers, and the activity were classified as heavy, and have caused the worst postures, especially in relation to the lumbar spine of workers. Hip and shoulders were the most affected articulations in the execution of the pruning, but with little risk of damage to workers. Despite the higher cost of production, the activities performed by semi-mechanized method provided several benefits such greater safety, health and quality of work, proving the viability of mechanization in forestry activities.